Effect of Laser Surface Treatment on Some Mechanical Properties of Low Carbon Steel - Asaad K. Hamza; Enaam O.Hasuon; Khansaa D. Salman (Engineering and Technology Journal, 2012)
This research aims to study the effect of localized laser surface treatment onmechanical behavior of low carbon steel. Laser Cw Nd : YAG was used in thetreatment hardening of the specimens for different laser energy (2.7,3.3,4.37100J ),with time interval for the beam (10-2 sec) and the laser intensity(4500,5500,7100Watt/mm2) . Different mechanical tests were achieved Static and Dynamic on thespecimens which were surface treated .Static tests included ( Tensile test,Microhardness test) ,While the dynamic test included (Impact test ).The results show that the mechanical properties for low carbon steel H[.hxstrength by(0.9,10,25.5%) , ultimate tensile strength by(6.4,16.24,24.59%),while theincrement fracture stress by (12,17.28,34.87%),also increment in microhardness by(3.4, 5 , 23% )and toughness by (4.3,10.86,20.8 %). Some of mechanical propertiesfor low carbon steel reduce with increasing in laser energy which show in Youngmodulus (26.06,40.89,50.8%), Rigidity modulus by (25,40.5,48.99 %) , Poisson s,ratio (1.29,2.34,3.69%) .